2015
DOI: 10.1308/003588415x14181254789600
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of a myofibroma presenting on the tongue

Abstract: Myofibromas are benign neoplasms of myofibroblastic origin, rarely encountered in the oral cavity. Limited awareness of the clinical features of these lesions risks misdiagnosis of more sinister pathology. The objective of this report is to highlight the potential diversity of oral lesions by describing an uncommon presentation of a myofibroma. The case reveals the diagnostic difficulties encountered, along with postoperative complications, which exemplify the remarkable healing capacity of the oral cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
(10 reference statements)
0
7
0
1
Order By: Relevance
“…1,6 While soft tissue lesions mimic benign neoplasms due to their painless and slow growing characteristics, intra-osseous lesions usually destroy the adjacent bone, mimicking odontogenic tumors or malignant neoplasms. 1,6,7 Regardless of the type of lesion-soft tissue or intraosseous MF/MFT-the main clinical characteristic of our cases was a painless, slow growing mass. A benign neoplasm was the main diagnostic hypothesis among the cases of this systematic review, in addition to some characteristics of the bone lesions such as osseous destruction.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…1,6 While soft tissue lesions mimic benign neoplasms due to their painless and slow growing characteristics, intra-osseous lesions usually destroy the adjacent bone, mimicking odontogenic tumors or malignant neoplasms. 1,6,7 Regardless of the type of lesion-soft tissue or intraosseous MF/MFT-the main clinical characteristic of our cases was a painless, slow growing mass. A benign neoplasm was the main diagnostic hypothesis among the cases of this systematic review, in addition to some characteristics of the bone lesions such as osseous destruction.…”
Section: Discussionmentioning
confidence: 71%
“…The only patient that reported other body lesions was a boy, in agreement with the findings reported by Scheper et al 15 The literature shows that MF and MFT lesions may occur within a wide age range, being more common among infants and children. 7,9 The age of the patients included in this review showed a wide range.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apesar dos diversos diagnósticos diferenciais, a análise imuno-histoquímica é uma importante ferramenta para conclusão de um diagnóstico definitivo (CHATTARAJ M, et al, 2017; PEREIRA DE OLIVEIRA DHI, et al, 2019). Através da análise dos dados da imuno-histoquímica, o caso apresentado neste estudo possui uma concordância com a literatura, apresentando positividade para os antígenos de actina de músculos lisos, vimentina e HHF-35 e negatividade para desmina, S-100 e Ki-67 ( As complicações relacionadas ao tratamento do Miofibroma pouco são relatadas na literatura, geralmente quando a um envolvimento de um nervo pelo Miofibroma, levando a um dano do nervo ou sua remoção por parte do procedimento cirúrgico (SHARIFI A, et al, 2015;SHIBUYA Y, et al, 2008). No presente caso foi observado uma paralisia unilateral do nervo marginal da mandíbula, consequentemente a diminuição da motricidade da musculatura da mímica facial da região onde encontrava-se a lesão.…”
Section: Detalhamento Do Casounclassified